A population-based analysis of the effect of autologous hematopoietic cell transplant in the treatment of multiple myeloma. Issue 8 (August 2013) - Nivison-Smith, Ian; Simpson, Judy M.; Dodds, Anthony J.; Ma, David D. F.; Szer, Jeff; Bradstock, Kenneth F.
Abstract This population registry-based study followed all cases of myeloma diagnosed in New South Wales, Australia, during 2002–2005 and compared survival outcomes of those who proceeded to autologous hematopoietic cell transplant (HCT) with those who did not. Data available consisted of demographic details and survival, and did not include disease details or treatment type or response. Of 708 patients, 270 (38%) had a HCT. The 5-year overall survival (OS) of HCT recipients was significantly better than for those who did not proceed to HCT (62% vs. 54%, p = 0.003). HCT was a significant favorable risk factor for OS, while age over 60 was an adverse risk factor. However, for patients alive at 1 year from diagnosis, there was no significant difference in survival between HCT and non-HCT patients, suggesting that worse disease biology and/or coexisting morbidities were likely to be major reasons for the poorer outcome for non-HCT patients.